Contribution of the oxygen reduction reaction to the electrochemical cathodic partial reaction for Mg-Al-Ca solid solutions - Felten, Markus; Zhang, Siyuan; Changizi, Rasa; Scheu, Christina; Bruns, Mark; Strebl, Michael; Virtanen, Sannakaisa; Zander, Daniela (Electrochemistry Communications, 2023)
The electrochemical corrosion rate of magnesium depends on the stability of the surface layer formed. Based on the Mg substrate, the oxide structure comprises a dense MgO/Mg(OH)2 mixture underneath a porous plate-like Mg(OH)2 layer. While the kinetics of the anodic partial reaction have been mainly attributed to MgO, recent studies have showed an effect of the Mg(OH)2 layer thickness on the cathodic partial reaction. A thinner Mg(OH)2 layer has been associated with higher kinetics of the oxygen reduction reaction. In the present study, the mechanism has been further investigated via in situ respirometric measurements using Mg-Al-Ca solid solution in electrolytes with different pH values (pH = 8.0–13.0). The results indicate an additional effect based on the structure of the surface layer for Mg-Al-Ca alloys in the passive state. Furthermore, two different Al-enriched interfaces were observed and discussed in terms of their thermodynamic stability under alkaline immersion conditions.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Corrosion; Interfaces; Magnesium; ORR; TEM

Coupling Respirometric HER and ORR Monitoring with Electrochemical Measurements - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Electrochimica Acta, 2022)
An experimental setup for respirometric real-time monitoring of the kinetics of the H2 evolution reaction and the O2 reduction reaction coupled with electrochemical control is presented. Cathodic polarization of different metal electrodes was carried out to verify the accuracy, and sensitivity of this approach. It was found that the respirometric response was in excellent agreement with the applied electrical signal. Dissolution of H2 in the liquid phase can lead to a delayed detection of the evolved H2 in the gas phase. However, reducing the volume of electrolyte in the setup can diminish this lag in response time. The influence of H2 oxidation on reactive Pt and the generation of H2O2 on Au on the respirometric monitoring of cathodic reactions was investigated. Finally, the combined respirometric and electrochemical approach was applied to quantify dissolution of Al during cathodic polarization by relating the total cathodic charge with the electrical signal.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Cathodic corrosion; Electrode kinetics; HER and ORR real-time monitoring; Respirometric Method

Editors' Choice-Respirometric in Situ Methods for Real-Time Monitoring of Corrosion Rates: Part I. Atmospheric Corrosion - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2020)
A novel respirometric approach to monitor atmospheric corrosion kinetics is presented. Simultaneous real-time monitoring of the H-2 evolution reaction (HER) and the O-2 reduction reaction (ORR) is possible with a combination of optical O2 sensor measurements with gravimetric volume sensitive techniques or pressure sensor based techniques in closed chambers. The respirometric method is a universal, non-destructive tool applicable to any metal or alloy. It shows a high sensitivity for low corrosion rates and has a high time-resolution. Different examples of relevant engineering metals and alloys will be provided. Mass loss validation measurements carried out at the end of exposure show a good correlation with the total recorded cathodic charge. For metals with different oxidation states the average valency in the corrosion products can be calculated from the cathodic charge together with mass loss. The versatility of the novel monitoring technique is further demonstrated by studying the influence of wet-dry cycling, temperature steps or changes in the gas composition in situ. The rate of HER, ORR and total corrosion rate during these changing exposure conditions can be tracked directly on the same sample. Overall the new method contributes to bridging the gap between lab tests, accelerated testing and field exposure. (C) 2020 The Author(s). Published on behalf of The Electrochemical Society by IOP Publishing Limited.
CRIS-Team WoS Importer:2020-03-13

Electrochemical measurements used for assessment of corrosion and protection of metallic materials in the field: A critical review - Xia, Da Hai; Deng, Cheng Man; Macdonald, Digby; Jamali, Sina; Mills, Douglas; Luo, Jing Li; Strebl, Michael; Amiri, Mehdi; Jin, Weixian; Song, Shizhe; Hu, Wenbin (Journal of Materials Science & Technology, 2022)
Corrosion degradation is detrimental to metal structures as it shortens their lifetime and leads to huge economic losses and unexpected disasters. Therefore, the detection and monitoring of corrosion degradation is of great importance. Herein, we briefly review the state-of-the-art electrochemical methods, instrumentation (based on virtual instrumentation), and advanced sensor/probes that are used in the field for the assessment of corrosion damage. Typical corrosion monitoring results, some of which have been obtained at Tianjin University in the past 30 years, for metallic materials and organic coating/metal systems in atmospheric, marine, and soil conditions in the field are presented. Detection methods, data analysis, and theoretical and mathematical models regarding each corrosion system are discussed, and the challenges, problems and possible solutions for each case are suggested. Lastly, future developments, such as wireless, intelligent, and automatic electrochemical measurement, that will augment the present electrochemical methods of evaluating corrosion degradation are summarized.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Corrosion monitoring; Data analysis; Electrochemical method; In-situ measurement; Probe; Sensor; Virtual instrumentation

Mechanical properties of ultrafine-grained AlZnMg(Cu)-alloys AA7020 and AA7075 processed by accumulative roll bonding - Ruppert, Mathis; Strebl, Michael; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Science, 2015)
Ultrafine-grained AA7020 (AlZnMg) and AA7075 (AlZnMgCu) were produced by accumulative roll bonding (ARB) with up to 6 cycles. Different pre-heating treatments and their effect on the mechanical performance of the materials were investigated by means of hardness measurements and uniaxial tensile testing. It was found for AA7020 that by pre-heating at 230 degrees C for 2.5 min prior to each rolling step, an UTS of 550 MPa can be achieved, which is 51 % higher compared to the peak-aged T6 reference. For AA7075, pre-heating at 280 degrees C for 2.5 min leads to a very high UTS of 720 MPa after four ARB passes. A negative strain rate sensitivity was found for both alloys, which shifts toward zero with increasing number of ARB cycles. Post-ARB heat treatment was performed in order to overcome the reduced ductility after ARB. This leads to an enhanced strain hardening capacity after 4 cycles, resulting in an increase of the uniform elongation from 1.4 to 2.0 % for AA7020 and from 0.9 to 2.1 % for AA7075.

Real-Time Monitoring of Atmospheric Magnesium Alloy Corrosion - Strebl, Michael; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2018)
The atmospheric corrosion progress of Mg alloys is traditionally tracked by determining mass loss of the samples after exposure. This method provides only an average corrosion rate over the exposure time and is destructive. The work presented introduces a new non-destructive method for real-time monitoring of atmospheric Mg alloy corrosion rates based on the evolved hydrogen gas. This is realized with an adaption of the gravimetric hydrogen collection method. The effect of temperature and atmospheric pressure variations during the experiment can be compensated and reliable atmospheric hydrogen evolution rates can be measured. The new technique was applied to monitor real-time atmospheric corrosion rates of Mg alloys AZ31 and AZ91 with different amounts of NaCl contamination. Comparing the results of the gravimetric hydrogen method with mass loss experiments reveals a good correlation of the consumed charge over the total exposure time, thus validating the new technique. Evidence for the contribution of O2 reduction reaction to cathodic processes on Mg alloy atmospheric corrosion is presented. (C) The Author(s) 2018. Published by ECS.

Respirometric in Situ Methods for Real-Time Monitoring of Corrosion Rates: Part III. Deconvolution of Electrochemical Polarization Curves - Strebl, Michael; Bruns, Mark; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2023)
A highly sensitive respirometric method is presented that allows real-time monitoring of reaction rates involving H2 and O2 during electrochemical polarization. The measurement approach is based on simultaneous monitoring of the changes in the total pressure and the O2 partial pressure inside a closed chamber. Hence, it is possible to quantify the rates resulting from reactions such as HER, ORR and OER as a function of the applied potential. As a result, deconvolution of the net electric current into cathodic and anodic partial reaction rates during electrochemical polarization can be obtained. It was demonstrated that the respirometric monitoring approach can reveal superfluous cathodic reactions from Al during cathodic polarization as well as during anodic polarization of Al and Mg AZ31. Thus, the true metal oxidation rate could be determined from the electric current and the cathodic reaction rates. Furthermore, the rate of the HER during cathodic electrodeposition of Zn was measured. Through respirometric monitoring of Ni and stainless steel at high anodic potentials, the rate of O2 evolution could be distinguished from electrode oxidation processes.
CRIS-Team Scopus Importer:2023-06-23

Respirometric in situ methods for real-time monitoring of corrosion rates: Part II. Immersion - Strebl, Michael; Bruns, Mark; Schulze, G.; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2021)
With the aim to open a new window into corrosion processes this paper presents respirometric methods for real-time in situ monitoring of corrosion rates under immersion conditions. With these techniques, sensitive, non-destructive corrosion rate measurements are possible on basically all metals and alloys. Different methods are presented that enable to monitor HER, ORR or both reactions simultaneously based on the amount of evolved H2 or the amount of consumed O2 by volumetric, manometric and sensor-based approaches. Various research examples are presented, demonstrating the benefits and limitations of the different approaches. For Mg alloys, besides HER, ORR plays a role in the cathodic reactions and a good correlation of the total cathodic charge with mass loss was obtained. H2 dissolution into the electrolyte was identified as an important factor. The results obtained for Zn immersion corrosion in intermittent-flow and flow-through respirometric experiments suggest that the ORR mechanism leads to the generation of stable H2O2 under these conditions. As a result, the effective number of exchanged electrons for one O2 molecule was found to be in between two and four. The here introduced respirometric techniques allow new insights into corrosion mechanisms, in addition to enabling real-time monitoring of corrosion.
CRIS-Team Scopus Importer:2021-02-05